2002
DOI: 10.1046/j.1365-3032.2002.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

The function of female accessory reproductive gland secretion and a cost to polyandry in the yellow dung fly

Abstract: Abstract. Female yellow dung flies have large paired accessory reproductive glands, the function of which remains unclear. However, gland contents are secreted during copula and egg laying. Other female flies produce a range of anti-bacterial substances in their accessory reproductive glands that protect them and their eggs from pathogens, and it is possible that gland secretion acts similarly in yellow dung flies. A series of experiments was conducted to test this idea. Because the volume of secretion remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Tregenza et al (2003) found no simple benefits or costs of double versus single mating for females, but Hosken et al (2002) found that females mated once survived longer than those mated three times, suggesting that longevity costs are associated with multiple mating. There are physical costs of mating to females (Hammer 1941;Parker 1978a;Demont et al 2011).…”
Section: The Yellow Dung Fly As a Case Studymentioning
confidence: 99%
“…Tregenza et al (2003) found no simple benefits or costs of double versus single mating for females, but Hosken et al (2002) found that females mated once survived longer than those mated three times, suggesting that longevity costs are associated with multiple mating. There are physical costs of mating to females (Hammer 1941;Parker 1978a;Demont et al 2011).…”
Section: The Yellow Dung Fly As a Case Studymentioning
confidence: 99%
“…In contrast, only a few studies have examined polyandry in natural populations and reported benefits (Madsen et al 1992;Fisher et al 2006). In yellow dung flies, laboratory studies have shown that multiple mating is associated with longevity costs (Hosken et al 2002), but that females also benefit from polyandry: more successful males in sperm competition sire offspring that developed faster ). Here we document benefits of polyandry in a natural population: the proportion and the total number of emerged offspring increased significantly with the number of alleles (our proxy for the number of mating partners) detected within the sperm stores of females.…”
Section: Benefits Of Polyandrymentioning
confidence: 99%
“…The yellow dung fly is a naturally polyandrous species. Experiments with singly versus doubly mated yellow dung fly females have revealed no simple benefits or costs of multiple mating , but a study in which females mated once or three times revealed a longevity cost to females that copulated with more males (Hosken et al 2002). There is also some evidence that indirect benefits could offset this cost of mating: males that were more successful in sperm competition also had offspring that developed faster .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies of longevity costs of polyandry are currently restricted to invertebrates [9], [10], [14], [25], [26] probably because it is easier to monitor matings and survival parameters in these species. Therefore, although polyandry occurs in all groups of vertebrates [1], it remains unknown whether longevity costs of polyandry occur in these taxa [6].…”
Section: Introductionmentioning
confidence: 99%